Technology Transfer for Development: Insights from the Introduction of Low Cost Water Well Drilling Technology to Uganda - Danert, Kerstin (Cranfield University, 2003)
Third World development theory and practice are changing so rapidly that it is important to critically examine the fashions of today before they become history. This thesis considers the development, transfer, early adoption and sustainable use of technology, coupled with private sector participation in rural water supply provision. Improving water supplies for rural communities is one of the key challenges faced by development interventionists today. Lack of low cost, off the shelf technology for local enterprise which can provide affordable shallow wells for rural communities is one barrier to facilitating improvements. This thesis is based on research undertaken in Uganda to develop and transfer low cost water drilling technology in the context of decentralisation and privatisation policies. An extensive range of literature has been drawn together into 16 principles which guide technology transfer and development intervention. These principles are reexamined in the light of analysis of first hand experiences of undertaking a technology transfer project and interviews with stakeholders regarding their attitudes and perceptions. The research found that technology transfer is a cross-disciplinary and cross cultural process in which the linkages between the technology, context, individuals, organisations and beneficiaries need to be firmly established. Ugandan business and local Government culture plays a major role in facilitating successful technology uptake. Dealing with the risks associated with low cost groundwater technology is fundamental for its wider adoption. The process of technology transfer is important, particularly as high levels of stakeholder participation may compromise the delivery of outputs, at least in the short term. In terms of future challenges, this thesis shows that, culture, governance and equity need to be closely examined in relation to private sector participation in rural infrastructure provision. Private sector participation can conflict with community participation. How to adequately support innovation in Sub-Saharan Africa while harmonising development interventions is a challenge to the development community.